Crystal structure of 6,6′-((1E,1′E)-hydrazine-1,2-diylidenebis(methanylylidene))bis (3-(3-bromopropoxy)phenol), C20H22Br2N2O4 - Wang Zhi-Yong; Liu Yang; Yuan Jian-Ping; Zhang Qi-Long; Xu Hong; Huang Ya-Li (Zeitschrift für Kristallographie - New Crystal Structures)
C20H22Br2N2O4, triclinic, P1‾$P\overline{1}$ (no. 2), a = 5.0060(12) Å, b = 9.135(2) Å, c = 11.650(3) Å, V = 518.6(2) Å3, Z = 1, Rgt(F) = 0.0474, wRref(F2) = 0.1270, T = 273(2) K, β = 78.492(7).